Solving Quadratic Equations Using the Zero Product Property

Presentation on theme: "Solving Quadratic Equations Using the Zero Product Property"— Presentation transcript:

Solving Quadratic Equations Using the Zero Product Property

Can you solve the puzzle below. I’m thinking of two numbers
Can you solve the puzzle below? I’m thinking of two numbers. Their product is zero. Tell me one of the numbers.

Write, in your own words, why one of the numbers has to be zero.
Can you solve the puzzle below? I’m thinking of two numbers. Their product is zero. Tell me one of the numbers. Write, in your own words, why one of the numbers has to be zero.

Tell me the value of one of the variables.
Now, let’s think of this algebraically. AB=0 Tell me the value of one of the variables.

Does it matter which one of the variables is zero?
Could both of the variables be zero?

Complete the following:
Example 1 If (x-2) (x+3) = 0, then _____ = 0 or _____ = 0. Example 2 If x (x-1) = 0, then _____ = 0 or _____ = 0.

Now let’s apply this to solving some equations.
Example 3 (x-4) (x+2) = 0 The expressions have a zero product. x-4=0 or x+2=0 Therefore, one of the numbers must be zero. x=4 or x=-2 Since we do not know which one is equal to zero, we set them both equal to zero and we solve each expression for ‘x’.

Now try a few of these on your own.
Solve 1. (x-4)(x-5)=0 2. x(2x+2)(3x-1)=0 3. 2x(x+2)=0